PENGARUH PERSEPSI SISWA TENTANG KETERAMPILAN GURU MENJELASKAN DAN PENGGUNAAN MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS X DAN XI IPS DI SMA NEGERI 1 TIMPEH KABUPATEN DHARMASRAYA - Nurrahmah, Diny (Pendidikan Ekonomi, 2013)
ABSTRACTÂ This study aimed to determine (1) The effect of students perceptions of teachers skills to explain the results of the economic study class X and XI social sciences in SMA Negeri 1 Timpeh (2) The effect of the use of instructional media on learning outcomes economy class X and XI social sciences in SMA Negeri 1 Timpeh (3) The effect of students perceptions of teachers skills to explain and use of instructional media on learning outcomes economy class X and XI social sciences in SMA Negeri 1 Timpeh.This research is descriptive and associative with a quantitative approach. The study population was all students in classes X and XI social sciences SMA Negeri 1 Timpeh majoring in social studies totaling 167 people. Stratified sampling technique with random sampling with a sample size of 63 people. Techniques of data analysis: descriptive analysis and inductive analysis, the normality test, multikoleniaritas, homogeneity test, heteroscedasticity test and multiple regression analysis.From the results of the study found that students perceptions of teachers skills to explain and use of instructional media and a significant positive effect on learning outcomes economy class X and XI social sciences SMA Negeri 1 Timpeh, it can be seen from the value of F greater than F (8,776> 3,15). With a coefficient of determination of 22.60%, meaning that students perceptions of teachers skills to explain and use of instructional media for 22.60% effect on learning outcomes economy class X and XI social sciences in SMA Negeri 1 Timpeh.Â Key word: Skills to explain, the use of instructional media and outcomes economy.